Accelerated programmes in children's nursing to tackle the workforce gap in the United Kingdom: A cost-consequences analysis. (March 2020) - Benedetto, Valerio; Whittaker, Karen; Wilson, Neil; Storey, Hannah; Daune, Diane
Abstract: Background: With alarming vacancy rates and dipping availability of European nurses, remedies for the shortage of nurses in the UK are urged. To accelerate the registration of new children's nurses, a health education funder commissioned two education programmes within its region. The first is a 1-year programme designed for UK-registered nurses in adult or mental health. The second is a 2-year programme for individuals, not registered as nurses, who are child or social care graduates with experience of working with children and young people. Objectives: To evaluate the economic effectiveness of two accelerated children's nursing education programmes. Design: Economic evaluation. Settings: Two accelerated children's nursing education programmes in two sites in England. Participants: Nursing students enrolled in both programmes (N = 20). Methods: We adopt a cost-consequences analysis to analyse the programmes' costs and outcomes. Results: All graduates were heading for posts within the region where they studied, a favourable outcome for the funder. However, the first programme would deplete the workforce in other nursing fields, whereas the second, by quickening the graduates' career progression, would not dent the long-term shortage in entry roles. Given our small sample size, these impacts may differ if the programmes have wider implementation. Conclusions: Our evaluation measures the effectiveness of two novel accelerated education programmes in tackling the nurses' shortage. Concurrently, it contributes to developing a standardised approach for future economic evaluations in nursing education.